Treatment wetlands. - Kadlec, Robert H., 1938-; Wallace, Scott D., ....- (Boca Raton : CRC, 2009)
Completely revised and updated, Treatment Wetlands, Second Edition is still the most comprehensive resource available for the planning, design, and operation of wetland treatment systems. The book addresses the design, construction, and operation of wetlands for water pollution control. It presents the best current procedures for sizing these systems, and describing the intrinsic processes that combine to quantify performance. The Second Edition covers: New methods based on the latest research Wastewater characterization and regulatory framework analyses leading to detailed design and economics State-of-the-art procedures for analyzing hydraulics, hydrology, substrates and wetlands biogeochemistry Definition of performance expectations for traditional pollutants such as solids, oxygen demand, nutrients and pathogens, as well as for metals and a wide variety of individual organic and inorganic chemicals Discussion of methods of configuration, construction, and vegetation establishment and startup considerations Ancillary benefits of human use and wildlife habitat Specific examples of numerous applications Extensive reference base of current information The book provides a complete reference that includes: detailed information on wetland ecology, design for consistent performance, construction guidance and operational control through effective monitoring. Case histories of operational wetland treatment systems illustrate the variety of design approaches presented allowing you to tailor them to the needs of your wetlands treatment projects. The sheer amount of information found in Treatment Wetlands, Second Edition makes it the resource you will turn to again and again.